Manfaat Senam Hipertensi Air Rebusan Daun Salam terhadap Penurunan Tekanan Darah Lansia di Wilayah PKM Sirnajaya - Noviyanti, Lusi; Mutianingsih, Mutianingsih; Kartika, Iin Ira (Universitas Malahayati Lampung, 2024)
ABSTRAK The prevalence of hypertension in the elderly in the world according to WHO data is around 972 million people or 26.4%. People around the world suffer from hypertension, with the possibility that this figure will continue to increase by 2025 to as much as 29.2%. Of the 972 million people with hypertension. The purpose of this activity is to increase the knowledge of the elderly, families, cadres and the community about hypertension exercises and bay leaf boiled water which can be used as an alternative treatment for elderly people with hypertension. The method of implementation includes measuring blood pressure before carrying out activities, followed by counseling activities, demonstration of elderly gymnastics and demonstration of making bay leaf decoction and drinking bay leaf decoction water and finally measuring blood pressure. This community service activity was carried out on November 27, 2023, which was carried out in the work area of the Sirnajaya Health Center, Bekasi Regency, community service was carried out for 1 day. The results of community service show that the average systole before action is 116.7 mmHg, the average post test systole is 114.8 mmHg, the average pre test diastole is 81 mmHg and post test diastole is 79.9 mmHg. So the value of blood pressure both systole and diastole has decreased after doing anti-hypertensive exercises and drinking bay leaf decoction water. So it is recommended hypertension gymnastics and drinking boiled bay leaves to reduce high blood pressure as a non-pharmacological treatment. Keywords: Hypertension Gymnastics, Bay Leaf Boiled Water, Elderly Blood Pressure